2019
DOI: 10.1016/j.eurpolymj.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing microchamber arrays as a biodegradable drug depot system for implant coatings

Abstract:  A free-standing PLLA microchamber arrays films are proposed to deliver small watersoluble substances.  Rhodamine B was completely released from PLLA microchambers in vitro within 13 days.  Low frequency ultrasound damages PLLA microchambers and detaches a sufficient number of microchamber "caps" with prolonged exposure time.  Free-standing printed PLLA microchamber arrays can be applied as endovascular stent cover for complementary pharmacological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
1
25
0
1
Order By: Relevance
“…Incorporation of ZnO in PLA matrix provide control over surface topography and Mg degradation rate. A free-standing PLLA micro-chamber array was developed by dip coat PLLA solution on PDMS stamp followed by drug loading and sealing with pre-coated polymer substrate, for drug delivery application [ 82 ]. A low frequency ultrasound trigger the release of drug and in vitro test revealed that the full cargo of drug was completely released in 13 days under physiological condition.…”
Section: Other Biopolymer Coatingsmentioning
confidence: 99%
“…Incorporation of ZnO in PLA matrix provide control over surface topography and Mg degradation rate. A free-standing PLLA micro-chamber array was developed by dip coat PLLA solution on PDMS stamp followed by drug loading and sealing with pre-coated polymer substrate, for drug delivery application [ 82 ]. A low frequency ultrasound trigger the release of drug and in vitro test revealed that the full cargo of drug was completely released in 13 days under physiological condition.…”
Section: Other Biopolymer Coatingsmentioning
confidence: 99%
“…Rhodamine B was released within 13 days in a phosphate buffer solution. The PLA microchamber arrays can be applied as biodegradable drug depot system for the cover of implantable endovascular stent [ 223 ]. PLA/vancomycin-loaded noisome was designed through layer-by-layer nanocoating.…”
Section: Pla Applicationsmentioning
confidence: 99%
“…An increasingly interesting approach to improving AISI 316LVM lies in its functionalization with coatings intended to prolong its lifespan [ 10 , 11 ], increase fast osteointegration [ 12 ], and/or provide improved long-term corrosion resistance [ 13 , 14 ]. Various materials have been employed for this purpose (e.g., selenium nanoparticles [ 15 ], hydroxyapatite in various forms [ 16 , 17 ], polylactic acid [ 18 ], peptide coatings [ 19 ], etc.). However, it seems that most of the interest lies in biocompatible coatings based on polysaccharides, such as alginate (ALG), carboxymethyl cellulose (CMC), and others [ 12 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%